Collective household consumption behavior revealed preference analysis - Cherchye, Laurens; Rock, Bram De.; Vermeulen, Frederic (Hanover, Mass. Now Publishers, 2012)
We review a nonparametric "revealed preference" methodology for analyzing collective consumption behavior in practical applications. The methodology allows for accounting for externalities, public consumption, and the use of assignable quantity information in the consumption analysis. This provides a framework for empirically assessing welfare-related questions that are specific to the collective model of household consumption. As a first step, we discuss the testable necessary and sufficient conditions for data consistency with special cases of the collective model (e.g., the case with all goods publicly consumed, and the case with all goods privately consumed without externalities); these conditions can be checked by means of mixed integer (linear) programming (MIP) solution algorithms. Next, we focus on a testable necessary condition for the most general model in our setting (i.e., the case in which any good can be publicly consumed as well as privately consumed, possibly with externalities); again, this condition can be checked by means of MIP solution algorithms. Even though this general model imposes minimal structure a priori, we show that the MIP characterization allows for deriving bounds on the feasible income shares. Finally, we illustrate our methods by some empirical applications to data drawn from the Russian Longitudinal Monitoring Survey.
1. Introduction --Setting the stage: a revealed preference characterization of the unitary model --Rational collective consumption behavior -- 3.1 Individual preferences -- 3.2 Assignable quantities -- 3.3 Collective rationality -- 3.4 Revealed preference characterization -- 3.5 The sharing rule -- Testing and recovery results for the special -- Collective models -- 4.1 All goods are public -- 4.2 All goods private and no externalities -- 4.3 Extensions -- Testing and recovery results for the general -- Collective model -- 5.1 Testing -- 5.2 Recovery --Empirical applications -- 6.1 Data -- 6.2 The unitary model -- 6.3 The general collective model -- 6.4 The special collective models -- Conclusions -- A. Appendix -- References.
Includes bibliographical references (p. 307-312).
Laurens Cherchye, Bram De Rock and Frederic Vermeulen (2012) "Collective Household Consumption Behavior: Revealed Preference Analysis", Foundations and Trends in Econometrics: Vol. 4: No 4, pp 225-312.
Keywords: Consumption (Economics) -- Econometric models; Households -- Econometric models